Collective action for inclusive value-chain innovation: Implementation and results of the Participatory Market Chain Approach - Horton, D.; Devaux, A.; Thiele, Graham; Hareau, Guy; Ordinola, M.; López, G.; Mayanja, S.; Bernet, T. (International Potato Center, 2020)
Research and development approaches that incorporate elements of collective action, agricultural innovation systems, and value-chain development (VCD) are increasingly popular, but there has been little systematic analysis of their use and results. In this paper, we analyze experiences with a participatory approach for stimulating inclusive innovation in agricultural value chains, known as the Participatory Market Chain Approach (PMCA). Guided by a conceptual framework for analyzing PMCA interventions, we examine cases where the PMCA was applied in value chains for aquaculture, coffee, organic and typical regional products, potatoes and vegetables in Albania, Bangladesh, Bolivia, Indonesia, Nepal, Peru and Uganda. We find that the uses and results of the PMCA were strongly influenced by attributes of the external environment, the targeted value chain and the intervention in which the PMCA was applied. The PMCA has generally produced the most significant results where: (a) the agricultural and policy environment favored agricultural innovation and VCD; (b) the value chain offered significant potential for value addition or cost reduction; and (c) the PMCA was implemented with a high degree of fidelity to its basic principles in the context of a broader development effort. The active involvement of diverse stakeholders – not only smallholder producers but entrepreneurs along the value chain and relevant service providers – was crucial for stimulating innovation. Because innovation processes are complex and emergent in nature, local teams needed to develop flexible implementation plans and procedures that were adjusted over time in response to emerging opportunities and results. And because the PMCA requires the active engagement of value-chain actors and service providers with diverse, sometimes conflicting, interests, effective facilitation was crucial to the success of PMCA interventions. We found significant benefits of the PMCA frequently emerged long after the intervention had been implemented. This finding highlights the value of assessing interventions that support inclusive innovation several years after project funding ends. Notwithstanding the demonstrated utility of the PMCA in stimulating inclusive innovation in agricultural value chains, the approach has only achieved limited use beyond its original developers. This finding also reflects the both the lack of institutional support and an effective scaling strategy for the PMCA and the enduring challenges to mainstreaming participatory systems approaches in agricultural research and development organizations.